PVP-doped Cu-Mg binary metal electro-catalytic material as well as preparation method and application thereof

By doping magnesium and PVP in copper-based materials, the valence state of Cu+ is regulated, and nanosheet-like structures are generated through sodium borohydride reduction, the stability and selectivity problems of copper-based materials in electrocatalytic reduction of CO2 are solved, significantly improving the stability and selectivity of copper-based materials. The selectivity and Faraday efficiency of C2 products were obtained.

CN119265628AActive Publication Date: 2025-01-07CHINA UNIV OF PETROLEUM (BEIJING) +1

Patent Information

Application Number
CN202411405175.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Existing copper-based materials are difficult to maintain a stable intermediate valence state in the electrocatalytic reduction of CO2 reaction, resulting in low selectivity of C2 products and Faraday efficiency.

Method used

By doping alkaline earth metal magnesium and polymer PVP, the valence state of the copper-based material is regulated, and a Cu+ catalyst with nanosheet-like structure is reduced by sodium borohydride, thereby improving the selectivity and Faraday efficiency of C2 products.

Benefits of technology

The selectivity and Faraday efficiency of C2 products have been significantly improved. The Faraday efficiency of C2 products has been increased from 40.2% to 74.1%, and the Faraday efficiency of ethylene and ethanol has been nearly doubled, improving the application of copper-based in the field of electrocatalytic carbon dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265628A_ABST
    Figure CN119265628A_ABST
Patent Text Reader

Abstract

The invention provides a PVP-doped Cu-Mg binary metal electro-catalytic material and a preparation method and application thereof, and the preparation method comprises the following steps: dissolving copper chloride, polyvinylpyrrolidone and magnesium chloride in N, N-dimethylformamide to obtain a mixed solution; the molar ratio of the copper chloride to the magnesium chloride is 1: (0.98-1.02); and under the condition of ice-water bath, stirring the mixed solution, introducing protective gas, dropwise adding a sodium borohydride solution, generating a precipitate, separating, washing, and drying to obtain the PVP-doped Cu-Mg binary metal electro-catalytic material. By doping magnesium, controlling the doping amount of magnesium and combining PVP, the valence state of generated Cu < + > is effectively regulated and controlled, the selectivity of a C2 product is improved, meanwhile, the PVP coating the outer layer protects Cu < + > from being oxidized into Cu < 2 + >, and the stability of the material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a PVP-doped Cu-Mg binary metal electrocatalytic material and a preparation method and application thereof. Background Art

[0002] At present, the world's energy relies on fossil fuels, and the scarcity of fossil fuels has caused environmental problems and energy crises, which has caused great controversy. The exponential growth of the world's population has led to an increase in global energy consumption, and fossil fuels remain the main source to meet energy needs. However, the continued use of fossil fuels will produce a large amount of anthropogenic greenhouse gases. Renewable energy replacing fossil fuels can alleviate the environmental and energy crises to a certain extent, while modern renewable energy including hydropower, wind power, bioenergy, geothermal energy / ocean energy / solar energy accounted for only 11.2% of global energy consumption in 2019. Today, mitigating the emission of carbon dioxide in the atmosphere has become a key challenge facing the scientific community.

[0003] Electrocatalytic reduction of CO2 has attracted widespread attention as an efficient and convenient way to convert CO2. The products of electrocatalytic reduction of CO2 are rich, including carbon monoxide (CO), methane (CH4), formic acid (HCOOH), ethylene (C2H4), ethanol (C2H5OH), etc. C1 products such as carbon monoxide, methane, and formic acid have a Faraday efficiency of nearly 90% because they require fewer electrons in the reduction process and have a relatively simple reaction path. The generation of C2 products requires further CC coupling on the surface of the catalytic material, the reaction path is long, and the multi-electron process often requires a higher overpotential. Therefore, the Faraday efficiency of C2 products is often low and the product selectivity is poor. Among many catalytic materials, copper-based materials have moderate adsorption strength for *CO reaction intermediates, which is more conducive to CC coupling and easier to carry out. Therefore, copper has unparalleled advantages over other metal catalysts in producing C2 products.

[0004] The performance of directly using bulk polycrystalline copper as the working electrode in the electrocatalytic reduction of CO2 is poor. The yield of hydrogen, the competitive reaction product, is too high, and the carbon-containing products are mostly carbon monoxide, with less C2 products. Current research has shown that the factors that affect the selectivity of CO2 reduction products in copper-based materials include the size, morphology, crystal grain boundaries, element valence, etc. of the material, among which the zero-valent (Cu 0 ), divalent (Cu 2+ ) Intermediate valence copper (Cu + ) is more conducive to the formation of C2 products, while copper oxide (CuO) is more conducive to the production of methane. However, intermediate copper ions are difficult to prepare and it is difficult to maintain a stable intermediate valence state during the electrochemical reduction process. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a PVP-doped Cu-Mg binary metal electrocatalytic material and a preparation method and application thereof. The electrocatalytic material prepared by the method is a Cu-Mg binary metal electrocatalytic material that can be in a stable intermediate valence state (Cu + ) and using it as the cathode material for electrocatalytic carbon dioxide can effectively improve the selectivity of CO2 reduction to C2 products while maintaining stable catalytic performance of the material.

[0006] The present invention provides a method for preparing a PVP-doped Cu-Mg binary metal electrocatalytic material, comprising the following steps:

[0007] Dissolving copper chloride, polyvinyl pyrrolidone and magnesium chloride in N,N-dimethylformamide to obtain a mixed solution; the molar ratio of copper chloride to magnesium chloride is 1:0.98-1.02;

[0008] In an ice-water bath, the mixed solution is stirred and a protective gas is introduced, and a sodium borohydride solution is added dropwise to generate a precipitate, which is then separated, washed, and dried to obtain a PVP-doped Cu-Mg binary metal electrocatalytic material.

[0009] The present invention effectively regulates the valence state of the copper-based material by doping alkaline earth metal magnesium and PVP. Magnesium has a strong interaction with the *CO reaction intermediate, which can effectively promote carbon-carbon coupling in the carbon dioxide reduction process and improve the selectivity of C2 products. PVP is introduced in the preparation process, which has the advantages of low price and wide sources. The high molecular polymer PVP introduced in the reduction process ensures uniform dispersion during Mg doping and avoids agglomeration and oxidation. Divalent copper ions are reduced by potassium borohydride solution to successfully prepare a cross-linked nano-sheet structure copper-based catalytic material.

[0010] The cupric chloride, polyvinyl pyrrolidone, magnesium chloride and N,N-dimethylformamide described in the present invention are all commercially available products.

[0011] The present invention screens a series of alkaline earth metals Mg, Sr and Ba, and finds that magnesium atoms have a strong interaction with the *CO reaction intermediate, which can effectively promote carbon-carbon coupling in the carbon dioxide reduction process and improve the selectivity of C2 products. The molar ratio of copper chloride to magnesium chloride in the present invention is 1:0.98-1.02, preferably 1:1; the present invention adjusts the valence state of the copper-based catalytic material by adjusting the type and amount of alkaline earth metals to improve the selectivity of C2 products, wherein the C2 product is increased from 40.2% when magnesium is not added to 74.1% (FE C2H4 +FE C2H5OH +FE CH3CH2CH2OH ), the Faraday efficiency of ethylene and ethanol increased by nearly one-fold, significantly improving the application of copper-based electrocatalysis in the field of carbon dioxide.

[0012] The molar mass ratio of the copper chloride to the polyvinyl pyrrolidone in the present invention is 0.1 mmol:0.2 g.

[0013] The dosage ratio of N,N-dimethylformamide to copper chloride in the present invention is (14-16) mL:0.1 mmol, preferably 15 mL:0.1 mmol.

[0014] The concentration of the sodium borohydride solution in the present invention is 0.95-1.05 mol / L. In a specific embodiment, the concentration of the sodium borohydride solution is 1 mol / L.

[0015] The volume ratio of the sodium borohydride solution to N,N-dimethylformamide in the present invention is 4:3.

[0016] The present invention preferably uses deionized water and ethanol for washing in sequence; the number of washing times is at least 3 times.

[0017] The present invention preferably uses a vacuum oven for drying; the drying time is 5.5 to 6.5 hours, preferably 6 hours.

[0018] The present invention provides an electrocatalytic carbon dioxide battery cathode material, and the preparation raw materials include a PVP-doped Cu-Mg binary metal electrocatalytic material prepared by the preparation method described in the above technical scheme.

[0019] The raw materials for preparing the PVP-doped Cu-Mg binary metal electrocatalyst material of the present invention also include isopropanol and perfluorosulfonic acid resin;

[0020] The mass ratio of the PVP-doped Cu-Mg binary metal electrocatalyst material, the volume of isopropanol, and the volume ratio of the perfluorosulfonic acid resin is 0.005 g: (460-480) μL: (28-32) μL. In a specific embodiment of the present invention, the mass ratio of the PVP-doped Cu-Mg binary metal electrocatalyst material, the volume of isopropanol, and the volume ratio of the perfluorosulfonic acid resin is 0.005 g: 470 μL: 30 μL.

[0021] The present invention provides a method for preparing a PVP-doped Cu-Mg binary metal electrocatalyst material, comprising the following steps: dissolving cupric chloride, polyvinyl pyrrolidone and magnesium chloride in N,N-dimethylformamide to obtain a mixed solution; the molar ratio of the cupric chloride to the magnesium chloride is 1:0.98-1.02; stirring the mixed solution under ice-water bath conditions and introducing a protective gas, dropping a sodium borohydride solution to generate a precipitate, separating, washing and drying to obtain a PVP-doped Cu-Mg binary metal electrocatalyst material. The present invention effectively regulates the generation of Cu by doping magnesium and controlling its doping amount, and then combining PVP. +The valence state of the CuO2O3 increases the selectivity of the C2 product. At the same time, the PVP coated on the outer layer protects the CuO2O3 + Not oxidized to Cu 2+ , effectively improving the material stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Transmission electron microscope (TEM) images of the PVP-doped Cu-Mg binary metal electrocatalyst material prepared in Example 1 of the present invention at 100 nm and 2 nm;

[0023] Figure 2 This is an energy spectrum (EDS) analysis diagram of the PVP-doped Cu-Mg binary metal electrocatalyst material prepared in Example 1 of the present invention;

[0024] Figure 3 The X-ray diffraction pattern of the PVP-doped Cu-Mg binary metal electrocatalyst material prepared in Example 1 of the present invention;

[0025] Figure 4 The Faraday efficiency analysis results of the electrocatalytic materials prepared in Example 1 of the present invention and Comparative Example 4;

[0026] Figure 5 1 and 3, wherein (a) is the overall X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (b) is the Cu 2p X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (c) is the Cu LMN X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (d) is the Mg X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (e) is the overall X-ray photoelectron spectrum of the electrocatalytic material of Comparative Example 3, (f) is the Cu 2p X-ray photoelectron spectrum of the electrocatalytic material of Comparative Example 3, and (g) is the Cu LMN X-ray photoelectron spectrum of the electrocatalytic material of Comparative Example 3. DETAILED DESCRIPTION

[0027] In order to further illustrate the present invention, a PVP-doped Cu-Mg binary metal electrocatalytic material provided by the present invention and its preparation method and application are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0028] Example 1

[0029] 0.2 g PVP was added to 15 mL DMF solution and ultrasonicated. After the PVP was dissolved, 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.095 g (0.1 mmol) of anhydrous magnesium chloride were added. The mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas. 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. After the black precipitate was separated by centrifugation, it was washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a PVP-doped Cu-Mg binary metal electrocatalytic material.

[0030] Comparative Example 1

[0031] 0.2 g PVP was added to 15 mL DMF solution and ultrasonicated. After the PVP was dissolved, 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.0475 g (0.05 mmol) of anhydrous magnesium chloride were added. The mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas. 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. After the black precipitate was separated by centrifugation, it was washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a PVP-doped Cu-Mg binary metal electrocatalyst material.

[0032] Comparative Example 2

[0033] 0.2 g PVP was added to 15 mL DMF solution and ultrasonicated. After the PVP was dissolved, 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.1425 g (0.15 mmol) of anhydrous magnesium chloride were added. The mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas. 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. After the black precipitate was separated by centrifugation, it was washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a PVP-doped Cu-Mg binary metal electrocatalyst material.

[0034] Comparative Example 3

[0035] 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.1425 g (0.15 mmol) of anhydrous magnesium chloride were added to 15 mL of DMF solution, the mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas, and 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. The black precipitate was separated by centrifugation and washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a Cu-Mg binary metal electrocatalyst material.

[0036] Comparative Example 4

[0037] 0.17 g (0.1 mmol) of cupric chloride dihydrate was added to 15 mL of DMF solution, the mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas, and 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. The black precipitate was separated by centrifugation and washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a Cu-based electrocatalytic material.

[0038] Comparative Example 5

[0039] 0.2 g PVP was added to 15 mL DMF solution and ultrasonicated. After the PVP was dissolved, 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.16 g (0.1 mmol) of anhydrous strontium chloride were added. The mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas. 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. After the black precipitate was separated by centrifugation, it was washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a PVP-doped Cu-Sr binary metal electrocatalyst material.

[0040] Comparative Example 6

[0041] 0.2 g PVP was added to 15 mL DMF solution and ultrasonicated. After the PVP was dissolved, 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.21 g (0.1 mmol) of anhydrous barium chloride were added. The mixture was stirred in an ice-water bath environment and nitrogen was introduced as a protective gas. 20 mL of 1 mol / L sodium borohydride solution was slowly added dropwise. After a black precipitate was generated in the solution, stirring was continued for 8 h. After the black precipitate was separated by centrifugation, it was washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h to obtain a PVP-doped Cu-Ba binary metal electrocatalyst material.

[0042] Comparative Example 7

[0043] 0.2 g PVP was added to 15 mL DMF solution and ultrasonicated. After the PVP was dissolved, 0.17 g (0.1 mmol) of cupric chloride dihydrate and 0.095 g (0.1 mmol) of anhydrous magnesium chloride were added. The mixture was stirred in an ice-water bath and nitrogen was introduced as a protective gas. Stirring was continued for 8 h. The black precipitate was separated by centrifugation and washed three times with deionized water and ethanol respectively, and dried in a vacuum oven for 6 h. Due to the lack of sodium borohydride, the electrocatalytic material could not be synthesized.

[0044] Performance Testing

[0045] (1) Transmission electron microscopy (TEM) and energy dispersive spectrometer (EDS) analysis

[0046] The transmission electron microscopy (TEM) images of the PVP-doped Cu-Mg binary metal electrocatalyst material prepared in Example 1 at 100 nm and 2 nm show: Figure 1 ,Depend on Figure 1 It can be seen that the two-dimensional nanosheet metal catalytic material was successfully prepared by sodium borohydride reduction method, in which the Cu lattice is 0.213nm, which is Cu + , corresponding to its X-ray diffraction pattern ( Figure 3 ). Energy Dispersive Spectroscopy (EDS) analysis see Figure 2 ,Depend on Figure 2 It can be seen that the material contains elements C, N, O, Cu, and Mg, and each element is evenly distributed, indicating the successful dispersed incorporation of C and Mg elements. The dispersed incorporation of Mg is more conducive to the occurrence of CC coupling in the electrocatalytic CO2 reduction reaction.

[0047] (2) X-ray diffraction

[0048] The X-ray diffraction pattern of the PVP-doped Cu-Mg binary metal electrocatalyst material prepared in Example 1 is shown in Figure 3 It can be seen that the prepared Cu-based nanomaterials are mainly Cu2O, the materials without Mg and PVP are mainly divalent copper and monovalent Cu + More conducive to the selectivity of C2 products.

[0049] (3) Faraday efficiency analysis

[0050] Weigh 0.005g of the electrocatalytic materials prepared in Example 1 and Comparative Example 3, then add 470μL of isopropanol and 30μL of Nafion (perfluorosulfonic acid resin) and ultrasonically disperse them uniformly, then coat them uniformly on the surface of 0.5×1.5cm carbon paper and dry them at room temperature. The dried carbon paper is used as a working electrode.

[0051] The test system is a three-electrode system of a flow electrolytic cell, consisting of a working electrode, a reference electrode and a counter electrode. The reference electrode is Ag / AgCl (saturated KCl solution), the counter electrode is a commercial platinum sheet, and the working electrode is the prepared carbon paper.

[0052] The electrolyte was 50 mL of 0.5 mol / L potassium hydroxide solution, and CO2 was introduced at a flow rate of 15 mL / min. The linear sweep voltammetry (LSV) test was carried out on a CHI 660 electrochemical workstation with a scanning window of -0.6 to -2.5 V. The constant potential electrolysis experiment was carried out on a CHI 660 electrochemical workstation with a voltage setting range of -1.6 V to -2.4 V and a duration of 2 h. After the reaction started, the gas chromatograph was entered and samples were taken every 9 minutes. After the reaction was completed, the liquid in the cathode chamber was taken for nuclear magnetic resonance testing to determine the liquid phase product.

[0053] The Faraday efficiency analysis results of the electrocatalytic materials prepared in Example 1 and Comparative Example 4 are shown in Figure 4 , wherein (a) is the Faraday efficiency test result of the electrocatalytic material prepared in Example 1, and (b) is the Faraday efficiency test result of the electrocatalytic material prepared in Comparative Example 4. Figure 4 It can be seen that the prepared PVP-doped Cu-Mg two-dimensional nanometal material is more conducive to CC coupling in the electrocatalytic reduction of CO2 reaction, and can effectively improve the Faraday efficiency of the product. Compared with metallic Cu, the Faraday efficiency of PVP-doped Cu-Mg C2 product increased from 40.2% to 74.1%, and the Faraday efficiency of ethylene and ethanol increased by nearly one-fold.

[0054] In addition, the same method as above was used to analyze the Faraday efficiency of the electrocatalytic materials prepared in Comparative Examples 1 to 3 and Comparative Examples 5 to 6. The results showed that:

[0055] Comparative Example 1: A small amount of Mg doping cannot effectively promote CC coupling, and has no obvious effect on the metal d-band center of metal Cu. The Faraday efficiency of the C2 product is 43.8%, with no significant improvement.

[0056] Comparative Example 2: Excessive Mg incorporation leads to an intensification of the hydrogen evolution competition reaction, and the Faradaic efficiency of the C2 product is 56.2%, which is significantly lower than that of Example 1.

[0057] Comparative Example 3: The Cu-Mg binary metal material Mg without PVP formed obvious agglomeration and failed to be effectively dispersed, so that the valence state of Cu metal could not be effectively regulated, and the Faraday efficiency of its C2 product was 65.8%.

[0058] Comparative Example 5: The incorporation of metal Sr improves the selectivity of C2 product to a certain extent, and its C2 product Faraday efficiency is 54.1%, which is lower than that of Mg.

[0059] Comparative Example 6: The addition of metal Ba significantly improves CH4, but has a limited effect on the improvement of C2 products. The Faraday efficiency of C2 products is 50.6%, which is lower than that of Mg.

[0060] (4) X-ray photoelectron spectroscopy analysis

[0061] The X-ray photoelectron spectra of the electrocatalytic materials prepared in Example 1 and Comparative Example 3 are shown in Figure 5, wherein (a) is the total X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (b) is the Cu 2p X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (c) is the Cu LMN X-ray photoelectron spectrum of the electrocatalytic material of Example 1, (d) is the X-ray photoelectron spectrum of Mg, (e) is the total X-ray photoelectron spectrum of the electrocatalytic material of Comparative Example 3, (f) is the Cu 2p X-ray photoelectron spectrum of the electrocatalytic material of Comparative Example 3; (g) is the Cu LMN X-ray photoelectron spectrum of the electrocatalytic material of Comparative Example 3. It can be seen that the valence state of Cu in the PVP-doped Cu-Mg metal catalyst material is stable at Cu + , compared to Cu 0 Cu 2+ , Cu + It is more conducive to the occurrence of CC coupling, thereby effectively improving the selectivity of C2 products.

[0062] As can be seen from the above examples, the present invention incorporates alkaline earth metals (Mg, Sr, Ba) into copper-based catalysts by sodium borohydride reduction, demonstrating its influence on the catalyst mechanism of the catalytic material in the process of carbon dioxide reduction, among which magnesium has the most obvious effect on the improvement of C2 products. By incorporating high molecular polymer PVP, the doping and dispersion of alkaline earth metals are effectively guaranteed, avoiding their agglomeration and oxidation during the doping process. The alkaline earth metals and PVP incorporated effectively regulate the generation of Cu + The valence state of the C2 product is improved, and the selectivity of the C2 product is improved. At the same time, the PVP coated on the outer layer protects the Cu + Not oxidized to Cu 2 + , effectively improving the material stability.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a PVP-doped Cu-Mg binary metal electrocatalyst material, comprising the following steps: Dissolving copper chloride, polyvinyl pyrrolidone and magnesium chloride in N,N-dimethylformamide to obtain a mixed solution; the molar ratio of copper chloride to magnesium chloride is 1:0.98-1.02; In an ice-water bath, the mixed solution is stirred and a protective gas is introduced, and a sodium borohydride solution is added dropwise to generate a precipitate, which is then separated, washed, and dried to obtain a PVP-doped Cu-Mg binary metal electrocatalytic material.

2. The preparation method according to claim 1, characterized in that: The molar mass ratio of the copper chloride to polyvinyl pyrrolidone is 0.1 mmol:0.2 g.

3. The preparation method according to claim 1, characterized in that: The dosage ratio of the N,N-dimethylformamide and copper chloride is (14-16) mL:0.1 mmol.

4. The preparation method according to claim 1, characterized in that: The concentration of the sodium borohydride solution is 0.95-1.05 mol / L.

5. The preparation method according to claim 4, characterized in that: The volume ratio of the sodium borohydride solution to N,N-dimethylformamide is 4:

3.

6. A PVP-doped Cu-Mg binary metal electrocatalytic material, prepared by the preparation method according to any one of claims 1 to 5.

7. An electrocatalytic carbon dioxide battery cathode material, wherein the raw materials for preparation include the PVP-doped Cu-Mg binary metal electrocatalytic material prepared by the preparation method according to claim 1.

8. The cathode material for an electrocatalytic carbon dioxide cell according to claim 7, characterized in that: Also included are isopropyl alcohol and perfluorosulfonic acid resins; The mass ratio of the PVP-doped Cu-Mg binary metal electrocatalyst material, the volume of isopropanol and the volume ratio of the perfluorosulfonic acid resin is 0.005 g: (460-480) μL: (28-32) μL.

Citation Information

Patent Citations

  • Catalyst for preparing ethanol by electrically reducing CO and preparation method of catalyst

    CN114318378A

  • Non-metal doped copper-based catalytic material for electrocatalytic reduction of carbon dioxide as well as preparation method and application of non-metal doped copper-based catalytic material

    CN115710724A

  • Preparation and application of photocatalytic material with metal oxide as protective layer

    CN116586066A

Cited By

  • Synthetic method for in-situ construction of Cu &lt; + &gt; / Cu0 interface nano-catalyst based on heteroatom induction

    CN120250063A